High Electromagnetic Field Enhancement of TiO2 Nanotube Electrodes. Issue 24 (16th May 2018) - Öner, Ibrahim Halil; Querebillo, Christine Joy; David, Christin; Gernert, Ulrich; Walter, Carsten; Driess, Matthias; Leimkühler, Silke; Ly, Khoa Hoang; Weidinger, Inez M.
Abstract: We present the fabrication of TiO2 nanotube electrodes with high biocompatibility and extraordinary spectroscopic properties. Intense surface‐enhanced resonance Raman signals of the heme unit of the redox enzyme Cytochrome b5 were observed upon covalent immobilization of the protein matrix on the TiO2 surface, revealing overall preserved structural integrity and redox behavior. The enhancement factor could be rationally controlled by varying the electrode annealing temperature, reaching a record maximum value of over 70 at 475 °C. For the first time, such high values are reported for non‐directly surface‐interacting probes, for which the involvement of charge‐transfer processes in signal amplification can be excluded. The origin of the surface enhancement is exclusively attributed to enhanced localized electric fields resulting from the specific optical properties of the nanotubular geometry of the electrode. Abstract : TiO2 nanotubes are able to efficiently enhance light at the TiO2 –water interface. The unusual high electromagnetic enhancement arises from photonic crystal properties of the nanotubular geometry. Manipulation of the nanostructure allows application for surface‐enhanced Raman spectroscopy and bioelectrochemistry.